Elastisitas dan Upaya Pajak Bumi & Bangunan Perdesaan-Perkotaan (PBB-P2) terhadap Produk Domestik Regional Bruto (PDRB) Kota Banjarmasin - Ananda Rizky Meidiani; Saipudin Saipudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study uses a quantitative descriptive approach by analyzing the Elasticity and Efforts of Urban Land and Building Tax (PBB-P2) to GRDP in Banjarmasin City. The results obtained are: 1) the calculation of the elasticity of PBB-P2 on the GRDP of the city of Banjarmasin in 2014-2020 (7 years) has an average value of 4.60, which means that for every 1% change in PBB-P2 occurs, efforts can be made to increase GRDP by 4.60% so that the Government can optimizing potential tax opportunities as a multiplier effect on GRDP; 2) the calculation of PBB-P2 tax efforts on the GRDP of Banjarmasin City in 2013-2020 from year to year tend to have a relatively constant value, which ranges from 0.09 to 0.13 and has an average value of 0.11 or classified as very low, resulting in low awareness of the people of Banjarmasin City in paying taxes, especially PBB-P2 Banjarmasin City. In addition, there are a lot of vacant lands whose owners are outside the area, so Bakeuda Banjarmasin City has difficulty collecting PBB-P2.